Strategi Enkulturasi Nilai-Nilai Anti Tindakan Kekerasan Dalam Kehidupan Bermasyarakat, Berbangsa Dan Bernegara - Marzali, Amry (Studi Budaya Nusantara, 2017)
ABSTRACT Indonesian state was founded in the multicultural country setting to accommodate a wide range of diversity that exists in it. That is why, Pancasila chosen as as the national principle to govern the diverse lives of the people as a nation. However, during the life of this nation as Indonesian, it has shown that the ideals of multiculturalism is often marred by acts of violence caused by friction between elements that differs from each others. All this time, the strategy of handling conflict and violence is emphasised on prevention and public policy. This paper is intended to contribute thoughts about how the values of anti-acts of violence can be implanted and maintained in a multiethnic society. By looking at the "culture of of violence" in terms of three levels, i.e. the level of structural, cultural, and institutional, the strategy of enculturation of non-violence values got its differs forms.